Pengembangan Kompetensi Guru SD Muhammadiyah Merauke dalam Penerapan Konsep Dasar Ilmu Pengetahuan Sosial (IPS) Melalui Pendekatan Pembelajaran Kontekstual dan Inovatif - Hanip, Rival; Wahyudiono, Andhika; Nirtha, Eva; Bay, Rudolfus Ruma; Sinaga, Serlina Boru (Jurnal Pengabdian Masyarakat, 2024)
The disparity in the quality of Social Studies (IPS) education at SD Muhammadiyah Merauke is caused by the lack of teacher competence in contextual teaching methods, limited training, and insufficient facilities and government support. The purpose of this service is to enhance teachers' competencies in applying contextual and innovative Social Studies (IPS) teaching methods at SD Muhammadiyah Merauke. The implementation method was carried out in structured stages, starting with coordination with the school and local government. The workshop was conducted with lectures and hands-on practice to provide teachers with an understanding of the application of basic concepts of Social Education Science. (IPS). This activity took place at SD Muhammadiyah Merauke from October 10-15, 2024, with 10 teacher participants. After the workshop, a discussion was held to find solutions to the problems faced by teachers, such as limited facilities and low competence in contextual learning methods. The results of the community service conducted in the form of a workshop at SD Muhammadiyah Merauke successfully addressed several obstacles faced by teachers in implementing contextual and innovative learning. Through this workshop, teachers were provided training to enhance their competence in connecting Social Science Education (IPS) material with the context of students' daily lives. The participation of 10 teachers in this activity demonstrates enthusiasm for improving the quality of teaching. Although challenges related to facilities and understanding of local culture still exist, the success of this workshop demonstrates that proper training can have a positive impact on how teachers deliver material and enhance students' critical thinking skills. The conclusion of this service is that training and facility support are important for the implementation of contextual learning methods. Support from schools, the government, and the community is essential for the optimal implementation of teaching innovations.